(untitled) - Seltzer, Marsha Mailick; Krauss, Marty Wyngaarden (Washington, DC, 1994)
Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Older people with mental disabilities -- United States; Developmentally disabled older people -- United States; Người lớn tuổi -- Khuyết tật -- Hoa Kỳ